The Role of Customer-Focused Strategies to Improve Islamic Microfinance Institutions Performance: Empirical Evidence and Lessons from Yemen - Hoamid, Abdo Ali; Zain, Ali Yusob Md; Al-Matari, Yahya Ali; Minai, Mohd Sobri; Ahmad, Fais Bin (International Review of Management and Marketing, 2017)
Microfinance, a tool to fight poverty and to promote economic development, has attracted the attention of governments, international organizations, and academicians across the globe. Although the literature provides substantial evidence on the significant effects of the customer-focused strategies such as Total Quality Management (TQM) and Market Orientation (MO) on organizational performance, research on the role of these factors in the context of microfinance is still too limited, and in the field of Islamic microfinance is even more neglected. Moreover, empirical research related to these factors has shown that the findings are not conclusive, indicating the need for further research in the area. Thus, this study aims at examining the roles of TQM and MO on Islamic MFIs performance in Yemen which provides additional insights into the literature. Cross-sectional survey was employed, and questionnaires were administered to collect data from the branch managers of Islamic Microfinance Institutions in Yemen. Out of 93 questionnaires distributed through a self-administered approach, 71 usable responses were used for the analysis. Partial Least Square-Structural Equation Modeling was used and the results provide an empirical evidence of the significant roles of TQM and MO on the Islamic MFIs performance. The study is of great importance for academicians as it opens the door for further research into the area. It is also useful for practitioners as it provides empirical evidence on the significant roles of these strategies in achieving sustainability and better performance by Islamic MFIs in Yemen. These strategies are essential in establishing the platform for innovation to enable Islamic MFIs to develop and generate new Islamic financing products that satisfy Muslims entrepreneurs. Keywords: Total Quality Management, Market Orientation, Islamic Microfinance Institutions Performance, Yemen JEL Classifications: G21, L1, M3